2018
DOI: 10.1111/ijlh.12833
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency and clinical laboratory: Lessons revisited and clarified in seven questions

Abstract: The objective of this review article is to address the most frequently asked questions that pathologists and primary care physicians might face when dealing with a patient with suspicion of vitamin B12 deficiency. More specifically, the article mainly discusses the importance and prevalence of the deficit, how to recognize it, and the important role of a prompt diagnosis confirmation based on laboratory biomarkers for efficient replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Improvement of anemia and neurological status starts within weeks, but progress must be monitored carefully and treatment adapted if response is slow or fails to appear. Early diagnosis and treatment is essential since long‐standing, severe neurological disease tends to persist. There have been single pediatric cases with self‐limited movement disorders evolving when Cbl treatment for acquired deficiencies is started.…”
Section: Acquired Cbl Deficienciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvement of anemia and neurological status starts within weeks, but progress must be monitored carefully and treatment adapted if response is slow or fails to appear. Early diagnosis and treatment is essential since long‐standing, severe neurological disease tends to persist. There have been single pediatric cases with self‐limited movement disorders evolving when Cbl treatment for acquired deficiencies is started.…”
Section: Acquired Cbl Deficienciesmentioning
confidence: 99%
“…Optic neuropathy and impaired vision have been reported 18 . Combined spongy degeneration of the spinal cord due to demyelination is characteristic but not always present 3,4,15 . Neuropsychiatric complaints may be present in the absence of hematological symptoms, making mean corpuscular volume and hemoglobin poor screening parameters for Cbl deficiency [3][4][5]15 .…”
Section: Acquired Cbl Deficiencies: Background and Clinical Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperhomocysteinaemia has potential haemolytic effect by mechanisms involving both lipid peroxidation and membrane/cytoskeletal protein derangement,12 13 it activates coagulation and platelet aggregation and it impairs endothelial functions 14. Because hyperhomocysteinaemia occurs in most patients with functional vitamin B12 deficiency15 and higher susceptibility of structurally defective megaloblastic erythrocytes to damaged endothelium can be assumed in patients with vitamin B12 deficiency,16 it seems possible for microangiopathic haemolytic anaemia to occur in patients with vitamin B12 deficiency through hyperhomocysteinaemia. In addition, coexistence of methylene tetrahydrofolate reductase mutations with vitamin B12 deficiency seems related to pseudo-TMA due to vitamin B12 deficiency though hyperhomocysteinaemia16; conversely, one case of pseudo-TMA due to vitamin B12 deficiency without methylene tetrahydrofolate reductase mutations was also reported 17…”
Section: Discussionmentioning
confidence: 99%
“…In general, elevated levels of homocysteine and methylmalonic acid can be considered as sensitive indicators of functional vitamin B12 deficiency, because these have been proven as the markers of insufficient intracellular vitamin B12 15. In addition, based on a systematic review of case reports, elevated levels of homocysteine and methylmalonic acid were observed in around 94% of cases with pseudo-TMA due to vitamin B12 deficiency 18.…”
Section: Discussionmentioning
confidence: 99%